MODERASI PEMAHAMAN HIRARKI MAQĀSHID AL-SYARĪʻAH DALAM FIKIH PANDEMI PERSPEKTIF FIQH AL-AWLAWIYYĀT STUDI FATWA MUI - Siti Hajar; Ahmad Zaeni (Asy-Syari'ah, 2022)
The controversy about the al-Maqāshid al-Dlarūriyyah al-Khams hierarchy has an effect on the understanding of the Maqāshid al-Syarī'ah hierarchy in the MUI version of the Fiqh Pandemic, especially the fatwa on congregational and Friday prayers in mosques. In dzahir, the fatwa prioritizes hifdz al-nafs over hifdz al-dīn, while the majority of scholars are of the opinion that hifdz al-dīn occupies the highest hierarchy. This research aims to reveal a moderate understanding of the Maqāshid al-Syarī'ah hierarchy in Fiqh Pandemic from the perspective of Fiqh al-Awlawiyyāt. This research is qualitative by using Istiqrā, Muqāranah and Tawtsīqī methods. The results of this study are: first, the al-Tarjīh rule used by the theocentric group allows for a middle way to bring together views between theocentric and anthropocentric groups in determining the Maqāshid al-Syarī'ah hierarchy; second, Fiqh al-Awlawiyyāt is a comprehensive instrument to determine the Maqāshid al-Syarī'ah hierarchy in Pandemic Fiqh, because it accommodates the rules of al-Tarjīh, Fiqh al-Muwāzanah and Fiqh al-Taisīr wa Raf' al-Haraj, even in harmony with Fiqh al-̒Adzār through Qiyās Awlawī; third, Fiqh al-Awlawiyyāt becomes a middle ground for the controversy between theocentric and anthropocentric groups in the context of the Maqāshid al-Syarīʻah hierarchy. In conclusion, the Maqāshid al-Syarī'ah hierarchy in Pandemic Fiqh with the priority of hifdz al-nafs over hifdz al-dīn is set moderately by using Fiqh al-Awlawiyyāt.